POLA MAKAN DENGAN KEJADIAN KURANG ENERGI KRONIS PADA REMAJA PUTRI DI MADRASAH ALIYAH KANAENG TAKALAR: Eating Patterns with Chronic Deficiency of Energy in Adolescent Women at Madrasah Aliyah Kanaeng - Putri, Amelia Meike; Hartono, Rudy; Fanny, Lydia (Media Gizi Pangan, 2024)
Chronic Energy Deficiency (CED) is a condition where there is a chronic lack of food which can result in health problems. Factors that influence the occurrence of Chronic Energy Deficiency (CED) in a person are a lack of nutritional intake, either for economic reasons or psychosocial reasons such as appearance or body shape. This study aims to determine the relationship between eating patterns and the incidence of chronic energy deficiency in adolescent girls. This research is an analytical observational study using a cross sectional research design with a proportionate stratified random sampling method. The sample was 78 Madrasah Aliyah Kanaeng students who were selected as samples. The statistical analysis used is Chi Square. The results showed that the sample had a poor diet as many as 44 people (56.4%), the good diet category was 34 people (43.6%), the sample had a KEK nutritional status as many as 57 people (73.1%) and the normal category was as many as 21 people (26.9%). The results of statistical tests show that there is a significant relationship between diet and the incidence of chronic energy deficiency (p value = 0.048). Future research can conduct research on other factors that can influence the incidence of CED in adolescent girls besides diet